Design of a Carbon Monoxide Gas Measurement Tool Using Microcontroller-Based MQ-7 Gas Sensor in Households - Sugianto, Muhammad Agus; Zulfikar, Zulfikar (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
The increasing presence of carbon monoxide in residential environments poses a serious health risk due to its colorless, odorless, and tasteless nature. This study aims to develop and evaluate a carbon monoxide detection system using the MQ-7 sensor integrated with an Arduino microcontroller. The research employs an experimental design approach with a sequential development model, including system analysis, design, coding, and testing phases. The system is designed to detect carbon monoxide levels and provide early warnings using visual and auditory indicators. Testing results indicate that the system successfully detects varying concentrations of carbon monoxide with satisfactory accuracy and provides timely alerts. This study contributes significantly to household safety by offering a simple, effective, and affordable solution for carbon monoxide detection, thereby enhancing preventive measures against potential carbon monoxide exposure.